1993
DOI: 10.1002/hep.1840180305
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to core, envelope and nonstructural hepatitis C virus antigens: Comparison of immunocompetent and immunosuppressed patients

Abstract: Some immunosuppressed patients with hepatitis C virus infection do not have detectable levels of antibody to hepatitis C virus on second-generation enzyme immunoassay. Antibodies to the envelope and nonstructural region 5 proteins have not been examined. Four groups of patients with hepatitis C virus infection were studied: (a) 20 immunocompetent patients, (b) 15 hemodialysis patients, (c) 17 kidney transplant recipients and (d) 3 acute leukemia patients who underwent bone marrow transplantation. Serum samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 29 publications
4
49
1
1
Order By: Relevance
“…During this phase, detection of anti-HCV alone is insufficient to provide a diagnosis. 19 On the other hand, Tada et al 18 found no HCV-RNA-positive patient who tested negative by a second generation EIA. Most likely, the BMT patients in their study were no longer immunosupressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this phase, detection of anti-HCV alone is insufficient to provide a diagnosis. 19 On the other hand, Tada et al 18 found no HCV-RNA-positive patient who tested negative by a second generation EIA. Most likely, the BMT patients in their study were no longer immunosupressed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other papers analyze the results of serological tests in BMT and immunocompromised patients. 10,15,[17][18][19][20][21][22][23] Toma´s et al 23 found in a retrospective study of 61 BMT patients who had hepatic pathology, 29 patients with chronic hepatitis C of whom seven constantly tested anti-HCV negative but PCR positive. The Seattle group recommends hepatitis C testing, including viral RNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, they remain anti-HCV-negative despite being viremic, i.e. positive for HCV RNA, and the diagnosis of HCV infection would have been missed if only anti-HCV testing were performed (15)(16)(17)(18). Indeed, HCV RNA can be detected in about 9-18% of the anti-HCV-negative renal transplant recipients (16,19).…”
Section: Serologic and Virologic Test For Hcvmentioning
confidence: 99%
“…Replication of HCV is detectable only by the third generation EIAs that has been profoundly observed in hemodialysis and immunodepressed patients [13,14] . In a research study, Bcell epitopes and antigenic regions were recognized after cloning the genome of the HCV [6] .…”
Section: Diagnosismentioning
confidence: 99%